1996
DOI: 10.1111/j.1365-2958.1996.tb02629.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple copies of MATE elements support autonomous plasmid replication in Aspergillus nidulans

Abstract: The AMA1 sequence is an efficient plasmid replicator and transformation enhancer in Aspergillus nidulans. It comprises two long perfect inverted repeats (MATE elements) flanking a short, unique, central spacer. Subclone analysis indicates that the complete inverted duplication, but not the unique central spacer, is necessary for efficient plasmid replication. The smallest fragments able to affect transformation efficiency lie within the AT-rich portions of the inverted repeats. We demonstrate that two or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Rearranged plasmids that are easily recovered from stable transformants may result from the reiterated excision of integrated sequences rather than from the modification of self-replicating ones (No€ e el and Labar e ere, 1994). The transforming plasmids formed large concatemers in R. oryzae (Skory, 2002), as in other fungi (Aleksenko and Clutterbuck, 1995;Aleksenko et al, 1996;Barnes and MacDonald, 1986;Fierro et al, 1996).…”
Section: Plasmid Rearrangementsmentioning
confidence: 98%
“…Rearranged plasmids that are easily recovered from stable transformants may result from the reiterated excision of integrated sequences rather than from the modification of self-replicating ones (No€ e el and Labar e ere, 1994). The transforming plasmids formed large concatemers in R. oryzae (Skory, 2002), as in other fungi (Aleksenko and Clutterbuck, 1995;Aleksenko et al, 1996;Barnes and MacDonald, 1986;Fierro et al, 1996).…”
Section: Plasmid Rearrangementsmentioning
confidence: 98%
“…Inclusion of ans1 in transforming plasmids resulted in A. nidulans transformants that were mitotically stable with no evidence for autonomous replication, suggesting that this fragment promoted early integration (Ballance and Turner 1985). However, other studies have shown that the presence of ans1 led to the detection of high-molecular-weight extrachromosomal circular molecules in some A. nidulans transformants (Cullen et al 1987) and more recently Aleksenko et al (1996) reported that ans1, like a MATE element, could promote autonomous replication in A. nidulans and that this function could be enhanced when more than one copy was used. The trs elements are analogous to ans1, being AT-rich sequences which function as ARSs in S. cerevisiae and enhance transformation frequencies to a similar extent; therefore, they probably function by a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Although ans1 does not function as an ecient ARS in A. nidulans, it promotes early, stable integration of the transforming vector into the genome (Ballance and Turner 1985). High-molecular-weight extrachromosomal circular molecules were detected in some transformants with ans1 (Cullen et al 1987), and multiple copies of ans1 enhanced its ability to replicate extrachromosomally (Aleksenko et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore an alternative explanation is that telomere-promoted initiation of replication is inecient and error-prone and hence results in formation of aberrant, recombinogenic intermediates. This phenomenon is frequently observed whenever an inecient or impaired origin of replication is present on a plasmid (Aleksenko et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The transformation procedure was as described by Johnstone et al (1985). All other techniques have been described elsewhere (Aleksenko and Clutterbuck 1995;Aleksenko et al 1996).…”
Section: Strains Culture Conditions and Transformation Proceduresmentioning
confidence: 99%